VD_FINDINFO Décision / 2011 / 740 vom 12. Dezember 2011 - VD Tribunal cantonal (2011)
MOTIVATION DE LA DEMANDE, RADIATION DU RÔLE | 61 let. b LPGA, 27 al. 5 LPA-VD, 79 al. 1 LPA-VD, 94 al. 1 let. c LPA-VD